Generation of T Regulatory Cells in Children with Newly Diagnosed Type 1 Diabetes Mellitus - Łuczyński, W.; Wawrusiewicz-Kurylonek, N.; Szypowska, A.; Iłendo, E.; Bossowski, A.; Krętowski, A.; Stasiak-Barmuta, A. (Experimental and Clinical Endocrinology & Diabetes, 2012)
There is increasing evidence that T-regulatory (Treg) cells could be used to prevent or cure autoimmune diseases including type 1 diabetes mellitus (T1DM). The aim of the present study was to verify the hypothesis that functional Treg cells can be generated from conventional T-cells separated from a small amount of peripheral blood of children with newly diagnosed T1DM (N=25).CD4+CD25- cells were cultured with Treg expander (CD3/CD28) and IL-2 for generating de novo Treg cells. The assessment of the expression of selected genes and proteins critical to Treg function and the proliferation assays were performed with the use of real-time RT-PCR and flow cytometry.After a 4-week stimulation with Treg expander and IL-2, the percentage of T-regulatory cells was significantly higher compared to the cells treated with medium alone (with no difference between diabetic and control children). However, we found some disturbances in the gene expression at mRNA level for molecules crucial for T-reg function. The induced Tregs from diabetic and control children were fully functional as assessed in proliferation assays.despite some disturbances at mRNA level in the critical gene expression, the suppressive properties of induced Treg cells from diabetic and control children were effective.
Keywords: T regulatory cell; diabetes; children; immunotherapy; mRNA